Android apps development for image processing - Yin, Sihan (Nanyang Technological University, 2021)
'theEye' is an Android-based mobile image processing application designed and developed for this project. Its main features enable user to capture image with the device’s camera, select image from gallery, perform image processing functions, save, and share the processed image to various social media platforms such as Facebook, WhatsApp, and WeChat etc.